2009
DOI: 10.1080/15287390902841599
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Estimates of the Attributable Risk for Environmental and Genetic Risk Factors in Gastric Cancer in a Chinese Population

Abstract: Development of gastric cancer is a multistage, multifactorial process. This study determined the population attributable risk for environmental and genetic risk factors in development of gastric cancer. A 1:1 cancer case-control study was undertaken in Nanjing, Jiangsu Province, China. A conditional-logistic regression model was used to determine environmental and genetic risk factors and calculate attributable risk (AR%) for each environmental and genetic risk factor in gastric cancer. In addition, the summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…In a recent study, we noted that XRCC1 Arg194Trp was associated with GC risk in Sichuan, a western province in China (Wen et al, 2012). This is consistent with findings in two other studies for overall GC risk in Southwestern and Southeastern China (Shen et al, 2009;Yuan et al, 2010). However, contradictory results have been obtained in three Chinese studies focusing on association of XRCC1 Arg194Trp with cardia GC.…”
Section: Polymorphisms Of Xrcc1 and Adprt Genes And Risk Of Noncardiasupporting
confidence: 88%
See 1 more Smart Citation
“…In a recent study, we noted that XRCC1 Arg194Trp was associated with GC risk in Sichuan, a western province in China (Wen et al, 2012). This is consistent with findings in two other studies for overall GC risk in Southwestern and Southeastern China (Shen et al, 2009;Yuan et al, 2010). However, contradictory results have been obtained in three Chinese studies focusing on association of XRCC1 Arg194Trp with cardia GC.…”
Section: Polymorphisms Of Xrcc1 and Adprt Genes And Risk Of Noncardiasupporting
confidence: 88%
“…X-ray repair cross-complementing group 1 (XRCC1) and adenosine diphosphate ribosyl transferase (ADPRT) are two of many proteins involved in the BER pathway. Several genetic polymorphisms have been identified in both ADPRT and XRCC1 genes, of which XRCC1 Arg194Trp (C26304T) (Shen et al, 2000;Ratnasinghe et al, 2004;Liu et al, 2009;Shen et al, 2009;Yan et al, 2009;Yuan et al, 2010) and ADPRT Val762Ala (T2446C) Zhang et al, 2006;Zhang et al, 2009) have been widely studied for association with cardia and/or noncardia GC in the Chinese population, albeit with conflicting results reported.…”
Section: Polymorphisms Of Xrcc1 and Adprt Genes And Risk Of Noncardiamentioning
confidence: 99%
“…The XRCC1 Arg194Trp polymorphism with C to T transition at codon 194 is located at a conserved residue in humans (Lamerdin et al, 1995;Shen et al, 1998), and individuals with Arg/ Arg genotype exhibited highly increased chromosomal breaks (Vodicka et al, 2007). Since Shen et al (2000) suggested that XRCC1 Arg194Trp may be associated with risk of developing gastric cancer in a Chinese population, the association between XRCC1 Arg194Trp and gastric cancer (cardia and/or non-cardia cancers) has been investigated in different ethnicities (Shen et al, 2000;Lee et al, 2002;Ratnasinghe et al, 2004;Duarte et al, 2005;Hong et al, 2009;Liu et al, 2009;Shen et al, 2009;Yan et al, 2009;Palli et al, 2010;Yuan et al, 2010), though the results are conflicting. The ADPRT Val762Ala polymorphism with T to C transition at codon 762 is located in the sixth helix of catalytic domain that causes Val-to-Ala amino acid substitution.…”
Section: Adprtmentioning
confidence: 99%
“…However, the carcinogenesis of tobacco is relatively complex and the role of NAT2 described in different studies is not entirely consistent. In the studies concerning the association of NAT2 polymorphisms with the increased risk of gastric cancer, Shen et al (37) indicated that the rapid acetylator was the protective factor for the development of gastric cancer, whereas Ladero et al (38) suggested that it was regarded as a risk factor. However, results in other relevant studies demonstrated that no significant association between NAT2 polymorphisms and gastric cancer was found (37,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies concerning the association of NAT2 polymorphisms with the increased risk of gastric cancer, Shen et al (37) indicated that the rapid acetylator was the protective factor for the development of gastric cancer, whereas Ladero et al (38) suggested that it was regarded as a risk factor. However, results in other relevant studies demonstrated that no significant association between NAT2 polymorphisms and gastric cancer was found (37,39,40). This discrepancy has also existed in the studies of other tobacco-associated cancers, including lung cancer (41)(42)(43) and prostate cancer (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%